Beyond ‘ása ok álfa’ : Eddic Discourses of the Álfar and their Chthonic Semantic Centre - Nygaard, Simon (Religionsvidenskabeligt tidsskrift, 2022)
ABSTRACT: In the Poetic Edda, a multitude of understandings and ideas exist concerning the Otherworldly collective known as the álfar (Old Norse pl., sg. álfr). While the understandings are indeed many, they are not arbitrary. There seems to exist what Jens Peter Schjødt has termed a "semantic centre" for a number of "discourses" on the álfar. In this article, I will suggest various discourses of and construct a semantic centre for the álfar though an analysis of the stanzas of the Poetic Edda in which the álfar feature, supported when it is relevant by other Old Norse textual sources. I propose that constructing a semantic centre focusing on death and fertility, and thus viewing the álfar as chthonic beings, will help us make sense of the diversity in the discourses of the álfar in the eddic poems.